Evaluation of the impact of chronic wound treatment on the quality of life of patients in Ukraine based on the Wound-QoL-17 questionnaire - Homola, Dmytro; Kozynets, Georgiy (ScienceRise: Medical Science, 2025)
Chronic wounds represent a significant medical and social problem, substantially reducing patients’ health-related quality of life (HRQoL) across physical, emotional, functional, and social domains. Standardized questionnaires, particularly the Wound-QoL-17, are widely used internationally to assess HRQoL; however, studies in Ukraine remain scarce. Aim. To evaluate the impact of treatment based on the developed methodology for chronic wounds on patients’ HRQoL by assessing physical discomfort, emotional state, functional limitations, and socio-economic burden using the Wound-QoL-17 questionnaire. Materials and Methods. The study was conducted at the Burn Unit of the Municipal Non-Profit Enterprise “Medical Center of Kyiv City”. Patients with chronic wounds completed the Wound-QoL-17 questionnaire twice – at baseline and after wound healing. The questionnaire included 17 items covering key aspects of patients’ lives. Results. All 17 items showed statistically significant improvements (p < 0.001). The most pronounced effects were observed in pain reduction (3.25 ± 0.93 before vs. 1.56 ± 0.73 after treatment; d = 1.78), decreased dependence on others (3.12 ± 1.02 vs. 1.44 ± 0.51; d = 1.93), and reduced financial burden (for the healthcare system) (3.31 ± 1.14 vs. 1.62 ± 0.62; d = 1.57). Emotional well-being and functional activity also improved significantly, including mobility, stair climbing, and performance of daily activities. Conclusions. Treatment of chronic wounds leads to a comprehensive improvement in HRQoL, supported by statistically and clinically significant results. The Wound-QoL-17 questionnaire is a valid tool for evaluating treatment effectiveness and may be recommended for integration into Ukrainian healthcare practice